Intraocular Telescopic System Design: Optical and Visual Simulation in a Human Eye Model - Georgios Zoulinakis; Teresa Ferrer-Blasco (Journal of Ophthalmology)
Purpose. To design an intraocular telescopic system (ITS) for magnifying retinal image and to simulate its optical and visual performance after implantation in a human eye model. Methods. Design and simulation were carried out with a ray-tracing and optical design software. Two different ITS were designed, and their visual performance was simulated using the Liou-Brennan eye model. The difference between the ITS was their lenses’ placement in the eye model and their powers. Ray tracing in both centered and decentered situations was carried out for both ITS while visual Strehl ratio (VSOTF) was computed using custom-made MATLAB code. Results. The results show that between 0.4 and 0.8 mm of decentration, the VSOTF does not change much either for far or near target distances. The image projection for these decentrations is in the parafoveal zone, and the quality of the image projected is quite similar. Conclusion. Both systems display similar quality while they differ in size; therefore, the choice between them would need to take into account specific parameters from the patient’s eye. Quality does not change too much between 0.4 and 0.8 mm of decentration for either system which gives flexibility to the clinician to adjust decentration to avoid areas of retinal damage.